Distribution of gold nanoparticles into the brain: a systematic review and meta-analysis. Issue 8 (14th September 2021) - Behroozi, Zahra; Rahimi, Behnaz; Kookli, Keihan; Safari, Mohammad S.; Hamblin, Michael R.; Razmgir, Maryam; Janzadeh, Atousa; Ramezani, Fatemeh
Abstract: Despite the widespread use of gold nanoparticles (GNPs), there is no consensus on their distribution to different tissues and organs. The present systematic review and meta-analysis addresses the accumulation of GNPs in brain tissue. Extensive searches were conducted in electronic databases, Medline, Web of Science, EMBASE, and Scopus. Based on inclusion and exclusion criteria, primary and secondary screening was performed. The value of brain accumulation of gold nanoparticle (the percentage of the injection dose of GNPs/gram of brain tissue that applied as effect size (ES) in analysis) and the standard error of the mean were extracted from articles and analyzed by calculating the pooled ES and the pooled confidence interval (CI) using STATA software. p   ≤ 0.05 was considered significant. Thirty-eight studies were included in the meta-analysis. The results showed that the amount of GNPs was 0.06% of the injection dose/gram of brain tissue (ES = 0.06, %95 CI: 0.06–0.06, p  < 0.0001). Considering the time between injection and tissue harvest (follow-up time), after 1 h the GNPs in brain tissue was 0.288% of the injection dose/gram of tissue (ES = 0.29, 95% CI: 0.25–0.33, p  < 0.0001), while after four weeks it was only 0.02% (ES = 0.02, 95% CI: 0.01–0.03, p  < 0.0001) of the injection dose/gram of tissue. The amount of GNPs in brain tissue was higher for PEG-coated GNPs compared to uncoated GNPs, and it was 5.6 times higher for rod-shaped GNPs compared to spherical GNPs. The mean amount of GNPs in the brain tissues of animals bearing a tumor was 5.8 times higher than in normal animals.